Kara pieniężna za naruszenie zakazu przemieszczania się przez osobę niepełnoletnią w stanie epidemii COVID-19 - Łątka, Monika (Czasopismo Prawa Karnego i Nauk Penalnych, 2021)
The paper concerns the possibility to impose a financial administrative penalty on a minor for a violation of the restriction on movement without the adult, which was introduced by the ministerial regulations. These provisions referred to the Tax Ordinance Act and did not include any exceptions related to, for example, the difficult situation of the minor’s family due to the epidemic outbreak. There was also a question of whether a minor can be held responsible for violation of such restriction. Equally impor- tant is the problem of applying lex mitior principle in administrative law and the issue of opportunism.